THE ANALYSIS OF LANGUAGE STYLE USED IN “USHI AND DUSHI” TALK SHOW WITH ADELE - Siti Aisyah Nurinsani Auliyah Burhan; Muftihaturrahmah Burhamzah; Rizki Fauzi (Faculty of Languages and Literature, Universitas Negeri Makassar, 2026)
Language style plays a crucial role in shaping communication dynamics in media, particularly in talk shows where formal and informal exchanges often coexist. However, limited studies have explored how language styles manifest in humorous interview formats, revealing a gap between theoretical classifications and real-life applications. This study aims to examine the language styles employed in the “Ushi and Dushi” talk show episode featuring Adele. Using a qualitative descriptive method, the research involved downloading and transcribing the episode from YouTube to analyze the verbal interactions between the host (Ushi) and the guest (Adele). The dialogues were categorized based on Joos’ (1967) five language style classifications: frozen, formal, consultative, casual, and intimate. The analysis identified 17 instances of language style use, consisting of 1 formal, 8 casual, 2 consultative, 2 frozen, and 4 intimate styles. The findings reveal that casual style is predominantly used by the host, contributing to the comedic and informal tone of the show, whereas the interviewee primarily employs formal style, possibly due to the structured setting resembling a news broadcast. This contrast illustrates the interplay between setting, role, and communicative intent in shaping linguistic choices. The study concludes that even in entertainment-focused formats, language style serves strategic functions and is influenced by both context and participant roles, offering valuable insight into pragmatic language use in media discourse.